2022
DOI: 10.1007/s11427-022-2161-3
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of aging

Abstract: Aging is characterized by a progressive deterioration of physiological integrity, leading to impaired functional ability and ultimately increased susceptibility to death. It is a major risk factor for chronic human diseases, including cardiovascular disease, diabetes, neurological degeneration, and cancer. Therefore, the growing emphasis on “healthy aging” raises a series of important questions in life and social sciences. In recent years, there has been unprecedented progress in aging research, particularly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(99 citation statements)
references
References 1,089 publications
0
77
0
2
Order By: Relevance
“…155,157 Senescent cells induce the formation of a complex, multicomponent SASP by secreting a range of cytokines, inflammatory factors, and adhesion factors. 158 In the local microenvironment, the SASP alters the biological behavior of adjacent cells through autocrine and paracrine signaling. 158 For instance, a systemic environment that shapes aging-related diseases has been reported to exist, as the infusion of young cerebrospinal fluid (CSF) improves the memory function of aged brains.…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
See 2 more Smart Citations
“…155,157 Senescent cells induce the formation of a complex, multicomponent SASP by secreting a range of cytokines, inflammatory factors, and adhesion factors. 158 In the local microenvironment, the SASP alters the biological behavior of adjacent cells through autocrine and paracrine signaling. 158 For instance, a systemic environment that shapes aging-related diseases has been reported to exist, as the infusion of young cerebrospinal fluid (CSF) improves the memory function of aged brains.…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
“…158 In the local microenvironment, the SASP alters the biological behavior of adjacent cells through autocrine and paracrine signaling. 158 For instance, a systemic environment that shapes aging-related diseases has been reported to exist, as the infusion of young cerebrospinal fluid (CSF) improves the memory function of aged brains. 159 This improvement is mainly mediated by serum response factor (SRF)-mediated oligodendrocyte progenitor cell (OPC) proliferation after exposure to young CSF.…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, investigations stand to identify age-associated underlying molecular processes mediating the beneficial effects of exercise, which in turn might help inform the development of strategies that promote healthy aging. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…Aging regulation is considered to utilize, at least part of the molecular mechanisms that control lineage determination and differentiation, as well as maintenance of cell identities in organogenesis and maturation during development, as some of which continued throughout the adult life ( 42–44 ). Recent studies have shown that some lineage-specific factors or genes during embryogenesis are repurposed in aging, suggesting an intrinsic link between lineage differentiation and aging ( 11 ).…”
Section: Database Content and Usagementioning
confidence: 99%